2021
DOI: 10.1177/20552173211062142
|View full text |Cite
|
Sign up to set email alerts
|

Determining the best window for BNT162b2 mRNA vaccination for SARS-CoV-2 in patients with multiple sclerosis receiving anti-CD20 therapy

Abstract: We studied the serologic response to the BNT162b2 mRNA vaccine at four weeks after the second dose in patients with RRMS treated with rituximab with extended-interval dosing ( n = 26). At four weeks, 73% of patients were seropositive. No patient without B cells at the first dose ( n = 4) was seropositive. Four of seven (57%) patients with B-cell proportion >0% and ≤5% were seropositive. All patients with B-cell proportion >5% ( n = 15) were seropositive. In all patients, quantitative ELISA measures after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
(13 reference statements)
0
9
0
1
Order By: Relevance
“…Some studies report that the timing of vaccination versus infusion affects the likelihood of seropositivity, whereas others do not. The presence of CD19 + and/or CD20 + cells were associated with an increased likelihood of antibody response in some studies 9–12,16,17 but not in others 18,19,36 ; the presence of CD19 + /CD20 + cells is somewhat correlated with timing 11,15,17,19,50 but was not consistently in all patients 16 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some studies report that the timing of vaccination versus infusion affects the likelihood of seropositivity, whereas others do not. The presence of CD19 + and/or CD20 + cells were associated with an increased likelihood of antibody response in some studies 9–12,16,17 but not in others 18,19,36 ; the presence of CD19 + /CD20 + cells is somewhat correlated with timing 11,15,17,19,50 but was not consistently in all patients 16 …”
Section: Discussionmentioning
confidence: 93%
“…1 ). 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 …”
Section: Resultsunclassified
“…With the outbreak of the COVID‐19 pandemic, concerns were raised regarding the impact of BCDTs on humoral and cellular immune response to SARS‐CoV‐2 infection and vaccination [ 3 ]. Since then, several studies have reported a blunted antibody response, albeit a largely intact T‐cell response, in persons with MS (pwMS) treated with BCDTs [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 12 ]. Failure to seroconvert has in particular been observed in pwMS who received an anti‐CD20 infusion close to the time of vaccination [ 4 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a correlation between time since last dose and B‐cell repletion exists at the group level, variable total treatment duration and individual differences may impact on B‐cell repopulation dynamics [ 17 ]. Therefore, an ideal dosing interval to optimize vaccine response that fits all patients seems unlikely, and there is a need for robust biomarkers that can predict vaccine efficacy while maintaining the effect of anti‐CD20 treatment on relapse rates [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that even minimal B-cell reconstitution may correlate with an increased humoral response to COVID-19 vaccination. ( Disanto et al, 2021 , Apostolidis et al, 2021 , Rico et al, 2021 , van Kempen et al, 2021 ) In one study, while 1 of 36 patients with undetectable B cells seroconverted after vaccination, 45% of patients with between 0 and 1% of CD19+ B cells seroconverted. ( Mrak et al, 2021 ) Studies have also found a significant correlation between time since last anti-CD20 infusion as well as length of anti-CD20 therapy and SARS-CoV-2 antibody titer.…”
Section: Introductionmentioning
confidence: 99%